2012
DOI: 10.1155/2012/916256
|View full text |Cite
|
Sign up to set email alerts
|

Plasmacytoid Melanoma of the Urinary Bladder and Lymph Nodes with Immunohistochemical Expression of Plasma Cell Markers Revealing Primary Esophageal Melanoma

Abstract: Plasmacytoid variant of melanoma is reported in only rare cases. We present the case of a 54-years-old man admitted for enlarged lymph nodes in the lumbar region. Initial diagnosis of plasmablastic lymphoma/plasma cell myeloma was considered. At our institute, a bladder polyp was removed. Microscopic exam demonstrated dense plasmacytoid cells infiltration with pigment deposits. Immunohistochemical study showed strong expression of HMB45, Melan A, and vimentin. There was focal positivity with S100 protein and C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
0
9
0
Order By: Relevance
“…However, histologically the tumor had features typical of plasmacytoma, which was also confirmed with MUM1 immunohistochemistry. Plasmacytoid melanoma comprised of cells expressing antigens characteristic of both tumors has been described in people, but MUM1 is absent in canine melanoma …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, histologically the tumor had features typical of plasmacytoma, which was also confirmed with MUM1 immunohistochemistry. Plasmacytoid melanoma comprised of cells expressing antigens characteristic of both tumors has been described in people, but MUM1 is absent in canine melanoma …”
Section: Discussionmentioning
confidence: 99%
“…Plasmacytoid melanoma comprised of cells expressing antigens characteristic of both tumors has been described in people, but MUM1 is absent in canine melanoma. 3,5 Additional stains to characterize the pigment showed a few cells positive with Prussian blue on cytology and histology preparations. Iron pigments have been identified rarely in benign and malignant plasma cells of people.…”
Section: Discussionmentioning
confidence: 99%
“…The plasma cell marker CD138 is commonly used in the diagnosis of plasma cell neoplasms such as multiple myeloma and extra-osseous plasmacytomas but has also been noted to be positive in occasional cases of plasmacytoid melanoma. 6 , 9 …”
Section: Discussionmentioning
confidence: 99%
“…Charfi et al [ 31 ] stated that plasmacytoid variant of melanoma is reported in only rare cases. They reported a 54-years-old man who was admitted because of enlarged lymph nodes in the lumbar region.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The diagnosis of metastatic plasmacytoid melanoma was finally established. Charfi et al [ 31 ] further stated the following. Clinical examination revealed an esophageal melanoma with melanosis which supported its primary location.…”
Section: Literature Reviewmentioning
confidence: 99%